Pengukuran Kinerja Saham Bank Digital di Indonesia dengan Model Capital Asset Pricing Model (CAPM) - Santoso, Budi; Sasmiharti, Juni (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
In general, when investors make investments, they certainly take into account the risks and returns from their investments, including investments in digital bank shares. To achieve profits from investments, CAPM (Capital Asset Pricing Model) can be used to predict stock performance. This is because CAPM is useful for determining stocks that are efficient and provide profits for investors. Because each digital bank stock has different performance, the CAPM that suits these conditions is CAPM SML (securities market line). This research uses a sample of 8 digital banks that have conducted an IPO (initial public offering) on the capital market. The research results show that of the 8 digital bank shares, 7 digital bank shares showed efficient stock performance and were able to provide profits. The 7 digital banks are AGRO, AMAR, ARTO, BABP, BBHI, BBYB, and BKSW. Meanwhile, one digital bank share, namely BACA, is the only bank whose shares are inefficient or have poor performance.